Pemilihan Kepala Derah Secara Langsung di Era Otonomi Luas - Ni'matul Huda (Universitas Islam Indonesia, 2004)
The discourse of regional (provincial and residential) leader direct election arises due to the miscellenaeus deviations apparent during the process of regional governors, residents or munipalcities across the country. This deviations may in the form of money politics, required documents falsification, the less capability (under minimum required standard), or because of either from political party or central government intervension, which are mostly are not parallel with the local people aspiration. There fore, through direct election, local people are able to directly choose the political leader they want.